Transcranial Magnetic Stimulation for Pain, Headache, and Comorbid Depression: INS‐NANS Expert Consensus Panel Review and Recommendation. Issue 3 (25th March 2020) - Leung, Albert; Shirvalkar, Prasad; Chen, Robert; Kuluva, Joshua; Vaninetti, Michael; Bermudes, Richard; Poree, Lawrence; Wassermann, Eric M.; Kopell, Brian; Levy, Robert; ,
Abstract : Background: While transcranial magnetic stimulation (TMS) has been studied for the treatment of psychiatric disorders, emerging evidence supports its use for pain and headache by stimulating either motor cortex (M1) or dorsolateral prefrontal cortex (DLPFC). However, its clinical implementation is hindered due to a lack of consensus in the quality of clinical evidence and treatment recommendation/guideline(s). Thus, working collaboratively, this multinational multidisciplinary expert panel aims to: 1) assess and rate the existing outcome evidence of TMS in various pain/headache conditions; 2) provide TMS treatment recommendation/guidelines for the evaluated conditions and comorbid depression; and 3) assess the cost‐effectiveness and technical issues relevant to the long‐term clinical implementation of TMS for pain and headache. Methods: Seven task groups were formed under the guidance of a 5‐member steering committee with four task groups assessing the utilization of TMS in the treatment of Neuropathic Pain (NP), Acute Pain, Primary Headache Disorders, and Posttraumatic Brain Injury related Headaches (PTBI‐HA), and remaining three assessing the treatment for both pain and comorbid depression, and the cost‐effectiveness and technological issues relevant to the treatment. Results: The panel rated the overall level of evidence and recommendability for clinical implementation of TMS as: 1) high and extremely/strongly for both NP and PTBI‐HA respectively; 2) moderate for postoperative pain and migraine prevention, and recommendable for migraine prevention. While the use of TMS for treating both pain and depression in one setting is clinically and financially sound, more studies are required to fully assess the long‐term benefit of the treatment for the two highly comorbid conditions, especially with neuronavigation. Conclusions: After extensive literature review, the panel provided recommendations and treatment guidelines for TMS in managing neuropathic pain and headaches. In addition, the panel also recommended more outcome and cost‐effectiveness studies to assess the feasibility of the long‐term clinical implementation of the treatment.